Uplatňování subjektivity ve výtvarné výchově na ZŠ - Malá, Tereza (Univerzita Karlova, Pedagogická fakulta, 2024)
Cílem bakalářské práce je zabývat se a zkoumat reálné uplatnění subjektivity ve výtvarné výchově u žáků druhého stupně základní školy. Praktická část bakalářské práce zahrnuje kvalitativní výzkum metodou rozhovorů se žáky a učiteli výtvarné výchovy základní školy, které budou analyzovány pomocí kvalitativní obsahové analýzy. Práce se zabývá tím, zda mají žáci, v rámci výtvarné výchovy na základní škole, možnost uplatnění vlastní subjektivity při tvorbě, dostatečný prostor pro sebevyjádření a jak na subjektivitu sami žáci nahlíží. Práce se dále zabývá i pohledem učitelů na subjektivitu ve výtvarné výchově, jak subjektivitu vlastně učitelé chápou, co pro ně znamená a jaký postoj k subjektivitě a jejímu uplatnění ve výtvarné výchově zaujímají. Výsledky této práce by mohly přispět k hlubšímu porozumění role subjektivity ve výtvarném procesu žáků a poskytnout vhled do vnímání subjektivity učiteli výtvarné výchovy. The goal of this bachelor's thesis is to address and explore the real application of subjectivity in art education among upper primary school students. The practical part of the thesis includes qualitative research through interviews with students and art teachers at primary schools, which will be analyzed using qualitative content analysis. The thesis investigates whether students have the opportunity to apply their own subjectivity in creation within art education at primary schools, sufficient space for self-expression, and how students themselves perceive subjectivity. Furthermore, the thesis also examines teachers' perspectives on subjectivity in art education, how teachers understand subjectivity, what it means to them, and their attitude towards the application of subjectivity in art education. The findings of this work could contribute to a deeper understanding of the role of subjectivity in the artistic process of students and provide insights into how subjectivity is perceived by art teachers. Katedra výtvarné výchovy Pedagogická fakulta Faculty of Education